By-Products of the Babassu Agribusiness for Ruminant Diets - Ygor Nascimento Portela; Danrley Martins Bandeira; Daniele de Jesus Ferreira; Henrique Nunes Parente; Michelle de Oliveira Maia Parente; Ivo Alexandre Leme da Cunha; Glayciane Costa Gois; Fleming Sena Campos; Francisca Claudia da Silva de Sousa; Luana Milena Pinheiro Rodrigues; Jessica Maria de Sousa Oliveira; Anderson de Moura Zanine (Scientifica)
The use of babassu agro-industrial residues in animal feed, in addition to being an economic option of great importance in reducing the environmental impact in regions of the Brazilian Cerrado, provides the production of good quality foods of animal origin due to its nutritional characteristics. However, information related to the nutritional components of babassu by-industrial residues has not yet been sufficiently explored. The aim of this study was to evaluate the nutritional potential of some by-products from the babassu production chain through chemical composition and in situ degradability analyses. The experiment was conducted in a completely randomized experimental design, with 4 by-products from babassu processing (cake, greasy, fine flour, and 95 µm flour) and 5 replications. The by-products differ in terms of chemical composition, except for the hemicellulose content. For the degradability of fraction “a” of dry matter, it presented a higher percentage for 95 µm flour. Fine flour and 95 µm flour presented the highest fractions “b” and “c,” potential, and effective degradability of dry matter. For the degradation of crude protein, the highest percentages of potential and effective degradability were observed for greasy and 95 µm flour. The highest standardized potentially degradable fraction and the highest passage rate were obtained by 95 µm flour, which also showed greater degradation for dry matter, crude protein, and neutral detergent fiber. Among the by-products studied, the babassu cake has superior chemical composition; however, the 95 µm flour presented nutritional value and satisfactory rumen degradation to be used as an additive or in partial replacement of traditional concentrates.